Applicability of Wagner's law in Zimbabwe - Mandishekwa, Robson (Journal of International Academic Research for Multidisciplinary, 2016)
The paper is aimed at finding out the applicability of Wagner’s law in Zimbabwe. A thorough background of Zimbabwe’s economy between 1960 to 2009 was given. Relevant literature relating Wagner’s law was given in which it was established that literature relating to Zimbabwe was scarce hence the need to carry out this study. The study employed simple Granger-causality test to validate the Law. It was revealed that Wagner’s law does not hold but the alternative, the Keynesian version was valid. Recommendations based on the results are then given, chief among them being that government should stimulate growth using its expenditure